BURNOUT SEBAGAI ‘UDZUR SYARI ISTRI DALAM RELASI SEKSUAL SUAMI ISTRI: PERSPEKTIF MARSALAH MURSALAH - Dewi Khusnul Kharomah; Faishal Agil Al Munawar; Kasuwi Saiban (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
This study aims to analyze the position of burnout as a ʿudhr sharʿī for wives in marital sexual relations from the perspective of maṣlaḥah mursalah. This research is normative in nature, employing conceptual and philosophical-normative approaches. The conceptual approach examines burnout from the perspective of modern psychology alongside the concepts of ʿudhr sharʿī, maṣlaḥah mursalah, and maqāṣid al-sharīʿah within Islamic legal thought. Meanwhile, the philosophical-normative approach assesses the compatibility of burnout with the objectives of Islamic law in protecting life, intellect, and human dignity. The findings indicate that although classical fiqh does not explicitly recognize mental exhaustion as a ʿudhr sharʿī, the fundamental principles of Islamic law provide a basis for legitimizing burnout as a valid excuse through a maṣlaḥah mursalah approach.